2006
DOI: 10.1523/jneurosci.5017-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Structural Determinants of M-Type KCNQ (Kv7) K+Channel Assembly

Abstract: The ability of KCNQ (K v 7) channels to form hetero-oligomers is of high physiological importance, because heteromers of KCNQ3 with KCNQ2 or KCNQ5 underlie the neuronal M-current, which modulates neuronal excitability. In KCNQ channels, we recently identified a C-terminal subunit interaction (si) domain that determines their subunit-specific assembly. Within this si domain, there are two motifs that comprise ϳ30 amino acid residues each and that exhibit a high probability for coiled-coil formation. Transfer of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
112
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(118 citation statements)
references
References 34 publications
5
112
1
Order By: Relevance
“…The impact of the C terminus was calculated assuming the previous figure for ER retention. The resulting figure (3.6) is similar to the reported impact on KCNQ3 surface expression of a cytosolic fragment of helix D from KCNQ2 (Schwake et al, 2006).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The impact of the C terminus was calculated assuming the previous figure for ER retention. The resulting figure (3.6) is similar to the reported impact on KCNQ3 surface expression of a cytosolic fragment of helix D from KCNQ2 (Schwake et al, 2006).…”
Section: Discussionsupporting
confidence: 81%
“…This is not, however, the only means of promoting KCNQ3 exit. It is well established that heteromerization of the C terminus plays a role on the surface expression increase after KCNQ2 and KCNQ3 assembly (Maljevic et al, 2003;Schwake et al, 2006;Nakajo and Kubo, 2008). Previously we showed that a chimeric subunit in which the C terminus of KCNQ3 was substituted for that of KCNQ2 also promoted the efficient traffic of KCNQ3 (Etxeberria et al, 2004), suggesting that a complex in which all subunits have alanine within the pore inner vestibule can still escape retention.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In contrast to the obligatory role of helices ABC for Kv7.2 channel function, helix D is dispensable (Schwake et al, 2006;Nakajo and Kubo, 2008). The helix D coiled-coil bundle has been largely considered as a passive stitch, with little active role other than to convey stability to the tetramer and specificity during the formation of heteromeric assemblies (Schmitt et al, 2000;Jenke et al, 2003;Maljevic et al, 2003;Schwake et al, 2006;Howard et al, 2007).…”
Section: Introductionmentioning
confidence: 99%